A Phylogenetically Conserved RNA Structure in the Poliovirus Open Reading Frame Inhibits the Antiviral Endoribonuclease RNase L - Han, Jian-Qiu (American Society for Microbiology, 2007)
RNase L is an antiviral endoribonuclease that cleaves viral mRNAs after single-stranded UA and UU dinucleotides. Poliovirus (PV) mRNA is surprisingly resistant to cleavage by RNase L due to an RNA structure in the 3C(Pro) open reading frame (ORF). The RNA structure associated with the inhibition of RNase L is phylogenetically conserved in group C enteroviruses, including PV type 1 (PV1), PV2, PV3, coxsackie A virus 11 (CAV11), CAV13, CAV17, CAV20, CAV21, and CAV24. The RNA structure is not present in other human enteroviruses (group A, B, or D enteroviruses). Coxsackievirus B3 mRNA and hepatitis C virus mRNA were fully sensitive to cleavage by RNase L. HeLa cells expressing either wild-type RNase L or a dominant-negative mutant RNase L were used to examine the effects of RNase L on PV replication. PV replication was not inhibited by RNase L activity, but rRNA cleavage characteristic of RNase L activity was detected late during the course of PV infection, after assembly of intracellular virus. Rather than inhibiting PV replication, RNase L activity was associated with larger plaques and better cell-to-cell spread. Mutations in the RNA structure associated with the inhibition of RNase L did not affect the magnitude of PV replication in HeLa cells expressing RNase L, consistent with the absence of observed RNase L activity until after virus assembly. Thus, PV carries an RNA structure in the 3C protease ORF that potently inhibits the endonuclease activity of RNase L, but this RNA structure does not prevent RNase L activity late during the course of infection, as virus assembly nears completion.